The Impact of Unplanned Pregnancy on Prenatal Attachment and Subjective Happiness - Ezgi Şahin; Esra Yurtsev; Saadet Yazıcı (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: Unplanned pregnancies are a major public health problem that causes undesirable socio-economic and psychological consequences for women, children and families in both developed and developing countries. This study was carried out to evaluate the impact of unplanned pregnancy on prenatal attachment and subjective happiness.Methods: This analytical cross-sectional study was conducted with 342 pregnant women who attended the Obstetrics and Gynecology outpatient clinic of a university hospital between July 2022 and October 2022. Data was collected using the Demographic Information Form, London Unplanned Pregnancy Determination Scale, Prenatal Attachment Inventory, and Subjective Happiness Scale. The data was evaluated using descriptive statistics, as well as pearson correlation and regression analyses.Results: Age, number of pregnancies, pregnancy week, feelings experienced upon learning of the pregnancy, and previous pregnancy loss status all appear to have a statistically significant effect on the prenatal attachment and subjective happiness scale (p